A multi-scalar, mixed methods framework for assessing rural communities' capacity for resilience, adaptation, and transformation. Issue 1 (1st January 2017) - Singh-Peterson, Lila; Underhill, Steven J. R.
Abstract: Resilience as a concept is often applied to address disaster risks and impacts. Metrics developed to measure the resilience of a community are often not applicable to other communities. In order for metrics to have utility and provide meaningful information to decision-makers, they need to be embedded within local contexts, be integrated across spatial scales, and address the community's capacity for adaptation and transformation, in addition to coping. To this end, we present an innovative framework to assess subtle variations in levels of community resilience at the household, community, and regional scale. Using a case study approach, we demonstrate how local actors can apply the framework to derive an applicable suite of locally relevant indicators. The main limitation in applying this, and other participatory methods, relates to difficulties in obtaining a representative level of participatory engagement, restricting the credibility of results and success of subsequent strategies.